The Utilization of Three Writing Schemes (TWS) in Teaching Essay Writing to UBSI Students in English Department - Yuskar, Bobby Octavia (CV. Creative Tugu Pena, 2024)
This research focuses on teaching essay writing utilizing Three Writing Schemes (TWS to students of UBSI from English Department. The subjects of this research are twenty students divided into two groups, ten male and ten female participants. Each student had to write an essay in classroom based on the instruction given by the lecturer. The method employed within this research is qualitative research that paid attention to the utilization Three Writing Schemes (TWS) as one of the techniques utilized by the researcher in teaching Essay Writing Class (EWC) to students of UBSI from English Department. Each scheme was interconnected to each other as unity that helped students to write an essay appropriately. The scoring was obtained according to the score from each method. This teaching technique was compiled by the researcher from a number of reliable resources, The Three Writing Scheme (TWS) as a solution to improve the writing skill when they write particular topic given in their essay class. There were numerous theories by the present study in order to have solid scientific background. The theories were taken from a number of scholars who already employed researches in teaching essay writing. The objective of this research is to provide applicable solutions to fellow lecturers in giving flexible schemes as an alternative in teaching essay writing to their students. Additionally, two previous researches were incorporated as significant contribution to enrich the quality of this research. Keywords: Three Writing Schemes, Teaching Essay Writing, Essay Writing Class